Decomposing Local: A Conjoint Analysis of Locally Produced Foods - Darby, Kim; Batte, Marvin T; Ernst, Stan; Roe, Brian (American journal of agricultural economics, 2008)
Increasingly, foods are marketed as "locally grown." We use stated preference data from a choice-based conjoint instrument to address two issues surrounding consumer demand for locally produced goods: (1) what is the geographical extent of "local," and (2) is the value consumers place on "local" production distinct from other factors that are often confounded with locally produced foods such as farm size and product freshness? We find our subjects place similar value on products produced "in state" and "nearby" and that consumers' willingness to pay for local production is independent from values associated with product freshness and farm size.